2019
DOI: 10.1007/s00520-019-04923-w
|View full text |Cite
|
Sign up to set email alerts
|

The relation between psychological profiles and quality of life in patients with lung cancer

Abstract: Objective Previous studies in patients with lung cancer examined the association between psychological factors with quality of life (QoL), as well as the association between psychological factors with sociodemographic and medical characteristics. However, knowledge about the impact of combinations of psychological characteristics on QoL is still lacking. Therefore, the current study aimed to identify psychological profiles, covering multiple psychological factors. Additionally, the association between these pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
1
10
1
Order By: Relevance
“…Compared to a recent study in Dutch patients with lung cancer, we observed a lower general health/QoL score (i.e., facet score of 7.0 (SD 1.4) versus 5.8 (SD 1.7) in this study) [39]. Probably this is due to the inclusion of solely patients with locally-advanced and metastatic lung cancer in our study whereas the referred study included patients with all stages of lung cancer with stage I and II comprising 45% of the study population.…”
Section: Linear Regression Analysescontrasting
confidence: 99%
“…Compared to a recent study in Dutch patients with lung cancer, we observed a lower general health/QoL score (i.e., facet score of 7.0 (SD 1.4) versus 5.8 (SD 1.7) in this study) [39]. Probably this is due to the inclusion of solely patients with locally-advanced and metastatic lung cancer in our study whereas the referred study included patients with all stages of lung cancer with stage I and II comprising 45% of the study population.…”
Section: Linear Regression Analysescontrasting
confidence: 99%
“…Moreover, among cancer patients, reduced social interaction may lead to the avoidance of potential stressors. As a result, they may receive lower levels of social support and develop SI (Lee et al., 2014; van Montfort et al., 2019). In particular, there was a strong and significant relationship between family support and SI among patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent studies among patients diagnosed with lung cancer indicate that those patients most frequently activate adaptive methods of coping with stress caused by their disease [42]. The task-oriented style is observed predominantly, while avoidant or emotion-oriented styles are less common.…”
Section: From Coping Styles To Stressmentioning
confidence: 99%